The Effect of Profitability and Leverage on Stock Returns in Banking Companies in Indonesia - Abdul Rahman (Jurnal Economic Resource, 2022)
This study analyzes the Effect of Profitability and Leverage on Stock Returns in Banking Companies Listed on the Indonesia Stock Exchange. The population used in this study were banking companies listed on the Indonesia Stock Exchange during 2013-2017, totaling eight companies. The type of data used is secondary data originating from the publication of annual reports of Banking Companies Listed on the Indonesia Stock Exchange for the 2013-2017 period. The analysis technique uses multiple linear regression analysis. The results showed that only the Return on Equity variable partially had a positive and significant effect on stock returns with an ROE value of less than 0.05. Meanwhile, the Debt-to-Equity Ratio variable negatively and significantly affects stock returns with a DER value of less than 0.05. The coefficient of determination shows a value of 0.634. This means that 63.4% of Return on Equity (ROE) is explained by the Profitability and Debt To Equity (DER) variables or Leverage variables. The remaining 36.6% is influenced by other factors not included in this research model.